Localization of the Trace Elements Iron, Zinc and Selenium in Relation to Anatomical Structures in Bovine Ovaries by X-Ray Fluorescence Imaging. (8th April 2015) - Ceko, Melanie J.; Hummitzsch, Katja; Bonner, Wendy M.; Aitken, Jade B.; Spiers, Kathryn M.; Rodgers, Raymond J.; Harris, Hugh H.
Abstract: X-ray fluorescence (XRF) was used to image 40 histological cross-sections of bovine ovaries ( n =19), focusing on structures including: antral follicles at different stages of growth or atresia, corpora lutea at three stages of development (II–IV), and capillaries, arterioles, and other blood vessels. This method identified three key trace elements [iron (Fe), zinc (Zn), and selenium (Se)] within the ovarian tissue which appeared to be localized to specific structures. Owing to minimal preprocessing of the ovaries, important high-resolution information regarding the spatial distribution of these elements was obtained with elemental trends and colocalizations of Fe and Zn apparent, as well as the infrequent appearance of Se surrounding the antrum of large follicles, as previously reported. The ability to use synchrotron radiation to measure trace element distributions in bovine ovaries at such high resolution and over such large areas could have a significant impact on understanding the mechanisms of ovarian development. This research is intended to form a baseline study of healthy ovaries which can later be extended to disease states, thereby improving our current understanding of infertility and endocrine diseases involving the ovary.